Impact of endometrial thickness and its combined effect with maternal age on singleton adverse neonatal outcomes in frozen–thawed embryo transfer cycles - Wang, Jie; Gao, Lina; Huang, Qiaoyun; Jiang, Weihua; Chen, Linjun; Wang, Shanshan (Frontiers in Endocrinology, 2025)
BackgroundThin endometrial thickness (EMT) and advanced age are both common risk factors for adverse neonatal outcomes (ANOs). However, studies evaluating the impact of EMT and combined effect of EMT and age on ANOs remain scarce with conflicts.MethodA retrospective cohort study was conducted on 7,715 singleton deliveries from frozen embryo transfer (FET) cycles between 2017 and 2021. The participants were categorized into four groups based on EMT quartiles (≤8.5, 8.6–9.5, 9.6–10.5, and >10.5 mm). The primary outcome was preterm birth (PTB), and the secondary outcome included early PTB (EPTB), small/large for gestational age (SGA/LGA), and low birth weight (LBW).ResultsBaseline characteristics were unevenly distributed across EMT groups. After adjusting for the confounders, EMT was found to be associated with the incidence of PTB (aOR 0.922, 95% CI 0.874–0.973, p = 0.003), EPTB (aOR 0.795, 95% CI 0.663–0.954, p = 0.014), LBW (aOR 0.886, 95% CI 0.796–0.986, p = 0.027), and LGA (aOR 1.038, 95% CI 1.004–1.074, p = 0.030). Furthermore, the rates of LBW in the group of EMT at 9.6–10.5 mm (aOR 0.551, 95% CI 0.339–0.895, p = 0.016) and >10.5 mm (aOR 0.536, 95% CI 0.332–0.865, p = 0.011) were lower compared to those with EMT ≤8.5 mm. Among women aged over 35, EMT of 9.6–10.5 mm was associated with a significantly lower incidence of LBW compared to thinner EMT, without increasing the risk of ANOs related to thicker EMT.ConclusionsOur study demonstrated the independent nonlinear impact of EMT on PTB, EPTB, LGA, and LBW. It provided new insights into the combined effects of EMT and age in FET cycles and offered valuable references for the clinical management and treatment strategies aimed at EMT.